THE SIGNIFICANCE OF COERCION IN THE IMPLEMENTATION OF STATE ADMINISTRATION: THE LEGAL CHARACTERISTICS OF CONVICTION - Jankal, Radoslav; Blikhar, Viacheslav; Syrovackyi, Valerii (Socio-economic relations in the digital society, 2023)
The article analyzes public administration as a complex process, the effectiveness of which must be ensured by a set of measures aimed at the state's performance of its functions. It is noted that the state is the organizer of social life, and it exercises its organizing influence through the exercise of power. That is, the state, through the adoption of laws, establishes norms of behavior in various spheres of society's life, and a person, obeying them, gets opportunities for development. However, not all citizens and persons who are in the territory of a certain state obey the legal state requirements, realizing the need to observe the established rules and models of behavior to achieve the common good. It is substantiated that legal nihilism, unlawful and deviant behavior, accompanied by the commission of a large number of offenses and crimes, negatively affect the state's ability to perform the functions assigned to it, to effectively carry out public administration. That is why today it is extremely important not only to find methods and methods that will increase the efficiency of state administration but also to find out their philosophical and legal foundations. This will make it possible to outline the philosophical foundations of the method or method itself, and will also help to reduce the level of its negative perception by society in general and by individual people or social groups in particular. In this context, it has been proven that one of such methods is state coercion as an activity of state bodies and officials authorized by law, which is carried out by influencing the physical, mental, organizational, or property state of legal subjects, with the aim of universally binding conscious fulfillment of requirements law, restoration of violated rights, as well as preventive activities of law enforcement agencies. On the basis of the conducted analysis, the data of the study were systematized, according to which the purpose of applying state coercion is to restore violated rights. That is when one person violates the rights and freedoms of another person or group of people, the state is obliged to respond to such actions. The state's reaction should be to restore the violated rights and freedoms as soon as possible and apply appropriate coercive measures to the offender.
Keywords: state; society; state administration; person; citizen; human rights; coercion; legal relations; law